Empirical Assesment of Service Quality Dimension in Technology-based Universities (Sains Humanika, 2012)
This study aims to verify the dimensionality of service quality within the context of Nigerian technological universities. Data for this study was collected from five public federal universities which are technology-oriented in Nigeria based on an adapted service quality questionnaire (ADSERVQUAL) from the original studies by Parasuraman et al. (1985, 1988). Respondents were students drawn from all faculties: engineering, management technology, environmental technology, science education, agricultural technology, pure and applied sciences and postgraduate studies. Factor analysis result gave rise to four dimensions from the 27 items of the ADSERVQUAL questionnaire, instead of the original five dimensions by Parasuraman et al. (1985, 1988). For this study, the four dimensions are named: empathy, tangibles, commitment and reliability. Dimensional analysis shows that students’ expectations were perceived to be higher than their perceptions of service quality, resulting to negative service quality perception. Therefore technological universities in Nigeria should strive towards reversing the negative perception of service quality by students in order to improve attachment. Managerial implication and suggestions for future research were made accordingly.
Keywords: Technological Universities; Nigeria; attachment